Intake of dietary branched-chain amino acids reduces odds of metabolic syndrome: a cross-sectional study on the PERSIAN Kavar cohort study - Shojaei-Zarghani, Sara; Fattahi, Mohammad Reza; Mansourabadi, Zahra; Safarpour, Ali Reza (Frontiers in Nutrition, 2024)
Background Metabolic syndrome (MetS) is identified by the manifestation of a minimum of three out of five metabolic abnormalities, including insulin resistance, hypertension, hypertriglyceridemia, abdominal obesity, and low levels of high-density lipoprotein cholesterol. The present study aimed to assess the association between dietary branched-chain amino acids (BCAA) intakes and MetS, due to available conflicting evidence. Methods A total of 4,860 individuals who had participated in the baseline phase of the PERSIAN (Prospective Epidemiological Research Studies in IrAN) Kavar cohort study were included in our study. The daily intake of valine, leucine, and isoleucine were evaluated using a semi-quantitative food frequency questionnaire. The association between dietary BCAA intake with MetS and its components was evaluated using logistic regression analysis. Results The mean intake of BCAA among the included subjects was 7.65 (standard deviation [SD]: 2.92), and the prevalence of MetS was found to be 49.2%. Multivariable logistic regression analysis revealed an inverse association between 1-S.D. increment in dietary valine (odds ratio [OR] = 0.85, 95% confidence interval [CI]: 0.78–0.94), leucine (OR = 0.85, 95% CI: 0.77–0.93), isoleucine (OR = 0.84, 95% CI: 0.76–0.93), and total BCAA (OR = 0.85, 95% CI: 0.77–0.93) intake and the odds of MetS. There were also a significant association between BCAA intakes and hyperglycemia and hypertriglyceridemia. Conclusion We observed a significant inverse association between dietary BCAA intake and MetS, hyperglycemia, and hypertriglyceridemia, regardless of confounding factors.